Progress in the analysis and design of marine structures : proceedings of the 6th International Conference on Marine Structures (MARSTRUCT 2017), May 8-10, 2017, Lisbon, Portugal /: proceedings of the 6th International Conference on Marine Structures (MARSTRUCT 2017), May 8-10, 2017, Lisbon, Portugal. (2017) - Unknown
No abstract available